2020
DOI: 10.1093/mnras/staa1466
|View full text |Cite|
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): assimilation of KiDS into the GAMA database

Abstract: ABSTRACT The Galaxy And Mass Assembly Survey (GAMA) covers five fields with highly complete spectroscopic coverage (>95 per cent) to intermediate depths (r < 19.8 or i < 19.0 mag), and collectively spans 250 deg2 of equatorial or southern sky. Four of the GAMA fields (G09, G12, G15, and G23) reside in the European Southern Observatory (ESO) VST KiDS and ESO VISTA VIKING survey footprints, which combined with our GALEX, WISE, and Herschel data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(132 citation statements)
references
References 71 publications
3
129
0
Order By: Relevance
“…The GAMA 23 photometry catalogue (Bellstedt et al 2020) contains measured properties and classifications of each object catalogued by the ProFound j (Robotham et al 2018) source finding routine, which uses a stacked r + Z image to perform initial source finding. Approximately 48 000 objects have spectroscopic redshifts provided by the Anglo-Australian Telescope (AAT), and the survey is ∼95% spectroscopically complete up to an i band magnitude of 19.5 (Liske et al 2015).…”
Section: Gama 23 Photometry Cataloguementioning
confidence: 99%
“…The GAMA 23 photometry catalogue (Bellstedt et al 2020) contains measured properties and classifications of each object catalogued by the ProFound j (Robotham et al 2018) source finding routine, which uses a stacked r + Z image to perform initial source finding. Approximately 48 000 objects have spectroscopic redshifts provided by the Anglo-Australian Telescope (AAT), and the survey is ∼95% spectroscopically complete up to an i band magnitude of 19.5 (Liske et al 2015).…”
Section: Gama 23 Photometry Cataloguementioning
confidence: 99%
“…While the merits and failings of these approaches can be argued -through numerous tests we have found that the P F approach is far less likely to go catastrophically wrong and produces more robust photometric measurements. For full details on P F and numerous tests, we refer the reader to the code description paper and four recent applications to the DEVILS input catalogue (Davies et al 2018), GAMA photometry (Bellstedt et al 2020), the VISTA VIKING datasets (Koushan et al 2021) and evolution of the high redshift stellar mass function (Adams et al 2020).…”
Section: The Need For a New Cosmos (D10) Photometric Cataloguementioning
confidence: 99%
“…With just these data products in hand, an extensive array of measurements can be made, such as stellar masses (Kauffmann et al 2003;Baldry et al 2010;Taylor et al 2015), star-formation rates (Brinchmann et al 2004;Davies et al 2016b) and star-formation histories (𝑒.𝑔. Kauffmann et al 2003;Bellstedt et al 2020, Thorne at al 2021, metallicities (.𝑒.𝑔. Tremonti et al 2004;Bellstedt et al 2021, Thorne et al in prep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the PROFOUND R package (Robotham et al 2018) is used to detect objects in the white-light image above a threshold of 3 × RMS sky and produce a preliminary segmentation map. Similarly to Bellstedt et al (2020), this segmentation map is then manually adjusted to join mistakenly split segments or remove visibly spurious detections. PROFOUND is used once more to finalise photometric properties using the r and i-band images, these include r e (approximate elliptical semi-major axis containing half the flux), photometric position angle (PA phot ), axis ratio and apparent magnitudes, for every object detected in the field.…”
Section: Source Detectionmentioning
confidence: 99%